High expression of YKT6 associated with progression and poor prognosis of hepatocellular carcinoma. (2nd November 2021) - Xu, Jia-Ze; Jiang, Jun-Jie; Xu, Hao-Jie; Sun, Xiao-Dong; Liu, Zheng-Chuang; Hu, Zhi-Ming
Abstract: Background and objective: The N-ethylmaleimide-sensitive fusion protein attachment protein receptor YKT6 is a key protein that controls the release of exosomes, was reported to play important roles in multiple cancers. However, the role of YKT6 in hepatocellular carcinoma (HCC) is still unknown. Methods: Here we first used bioinformatics tools to analyze the YKT6 mRNA expression in HCC. In addition, we retrospectively collected 330 cancer tissue specimens from HCC patients and 180 para-cancerous tissue specimens, and detected YKT6 expression using immunohistochemical staining. Then the relationship between YKT6 expression and the clinical characteristics of HCC was analyzed, Kaplan–Meier analysis and Cox regression model were also performed to evaluate the impact of YKT6 expression on prognosis of HCC. Protein-protein interaction network of YKT6, and the gene enrichment analysis (GSEA) database were used to predict possible signal pathways regulated by YKT6 in HCC. Results: The high expression rate of YKT6 in HCC (72.40%, 239/330) was higher than that in adjacent tissues (17.80%, 32/180, p  < .001), and high expression of YKT6 was correlated with tumor size ( p  = 0.002), Edmondson Grade ( p  < .001), metastasis ( p  < .001), microvascular invasion ( p  = .005), AFP level ( p  = .002). Kaplan–Meier survival analysis showed that HCC patients with high YKT6 expression level had poorer prognosis. Meanwhile, multivariate Cox regression analysis showed that Edmondson grade ( p  = .009), metastasis ( p  = .049), YKT6 expression ( p  = .037) are independent risk factors for poor prognosis of HCC. Conclusions: Our results suggested that the upregulated expression of YKT6 is closely related to the progression HCC, which may be used as a potential biomarker for poor prognosis in HCC.